A STUDY OF THE INFLUENCE OF KNOWLEDGE SHARING ON THE INNOVATION PERFORMANCE OF HIGH-TECH ENTERPRISES - Fan, Huawen (Journal of Buddhist Education and Research (JBER), 2022)
At present, market competition is intensifying. If companies would like to maintain long-term operations, they must continuously improve their own innovation performance and strengthen their core competitiveness. In the operation of an enterprise, knowledge sharing is an important condition for promoting the production of enterprises and their research and development, as well as an important link of enterprise knowledge management, and it has an important impact on the innovation performance of enterprises. At present, as companies continue to assume that knowledge sharing is concerned, it is of great value to study the impact of knowledge sharing on the innovation performance of high-tech enterprises. This article first elaborates that knowledge sharing has a significant positive impact on innovation performance and analyzes the empirical results and the role of knowledge sharing in improving innovation performance. Finally, it summarizes the full text and makes some suggestions. Based on the research results, some suggestions are put forward, including strengthening the incentives for employee knowledge sharing, creating a good knowledge sharing environment, strengthening human resource management, etc., to provide a certain reference for high-tech enterprises to improve their innovation performance.